Pertanggungjawaban Notaris terhadap Isi Akta Autentik yang Tidak Sesuai dengan Fakta - Amalia, Rizky; Musakkir, Musakkir; Muchtar, Syamsuddin (Fakultas Hukum, Universitas Muslim Indonesia, 2021)
In making an authentic deed, the Notary must guarantee certainty, order, and legal protection based on Law Number 2 of 2014. This research aims to determine the indicators so that the Notary can be held accountable for the contents of the Authentic Deed he made and explain the form of accountability that can be imposed on Notary regarding the contents of the Authentic Deed, which are inconsistent with the facts. The type of research used in this research is normative research and is supported by interview data. This study uses a statutory approach, a case approach, and a comparative approach. This study uses secondary data sources consisting of primary, secondary, and tertiary legal materials. The method of analysis in this study is to use qualitative analysis. The results show that the indicator so that the Notary can be held accountable for the contents of the Authentic Deed he makes is the intention or negligence of the Notary in making the authentic deed. Furthermore, the forms of accountability that can be passed on to the Notary for the contents of the Authentic Deed that are not following the facts, among others, are Civil, Criminal, and Administrative Liability/Code of Ethics. Based on these conclusions, it is recommended that notaries make authentic deeds based on morals, ethics and prudence, thoroughness, objectivity, and good faith to comply with all applicable legal provisions. Besides, it is necessary to renew the Law related to the cumulation or incorporation of the application of sanctions as a form of accountability for a notary public because the regulation of the cumulation or merger of the application of these sanctions will undoubtedly provide more protection and legal certainty for the injured parties, including the Notary itself.